2009
DOI: 10.1016/s0377-1237(09)80128-7
|View full text |Cite
|
Sign up to set email alerts
|

Midline Fractures in Single Maxillary Complete Acrylic vs Flexible Dentures

Abstract: Background: Patients using single maxillary denture against their natural mandibular teeth face the problem of midline fracture in their routine acrylic dentures. Various techniques have failed over the years to address the problem. In this study, flexible denture material (Lucitone) with injection moulding system has been used and evaluated for midline fracture in these patients. Methods: A total of 58 patients in the age group of 38 to 80 years, who had experienced midline fracture in their acrylic maxillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 14 publications
3
31
0
3
Order By: Relevance
“…These results were in accordance with the study conducted by Dhiman RK [16]. These findings may again be attributed to the basic nature of the denture base materials.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results were in accordance with the study conducted by Dhiman RK [16]. These findings may again be attributed to the basic nature of the denture base materials.…”
Section: Discussionsupporting
confidence: 92%
“…The result was in accordance with study by Shah J et al, [4] were flexible resin demonstrated lower hardness values and also possessed lower amounts of cross-linking agents, which -10]: Masticatory efficiency according to denture norms for wet carrots may affect surface hardness. As there was no statistically significant difference for masticatory performance of soft food between the conventional and flexible dentures, these flexible dentures with diet modification can be a better alternative to conventional dentures in patients with repeated midline fracture of denture, allergic to PMMA and denture sore mouth [3,16].…”
Section: Discussionmentioning
confidence: 99%
“…Većina relevantnih članaka prikazi su slučajeva ili serije prikaza slučajeva i u njima se vrjednuju fizikalnomehanička svojstava termoplastičnih materijala (11 -14). Kliničku učinkovi-tost i kako pacijenti prihvaćaju PDP-e ili PPP-e izrađene od najlona, u usporedbi s onima izrađenima od akrilatnih smola, procjenjivalo se tijekom 18 mjeseci u dva istraživanja (15,16). U prvom istraživanju (15) autori su izvijestili o samo dvije frakture po središnjoj liniji, dok su mastikacija, fonetika i tolerancija na nošenje bile poboljšane kod savitljivih gornjih pomičnih proteza uz prirodne zube u nasuprotnoj čeljusti.…”
Section: Uvodunclassified
“…However, many clinical studies including recent reports on the fracture of dentures during service indicated that mechanical properties of polymethyl methacrylate (PMMA) are not satisfactory in terms of longevity of the denture base [1][2][3][4][5] . Numerous attempts have been reported to improve the mechanical properties of the acrylic materials, but most of them were not transferred in clinical dentistry due to processing difficulties and high cost 6) .…”
Section: Introductionmentioning
confidence: 99%